Comparative effects of natural products on ischemia-reperfusion injury: relation to their "in vitro" antioxidant capacity - Fantinelli, Juliana Catalina (2016)
Our aim was to compare the effects of a non-alcoholic Cabernet-Sauvignon (CS), Malbec (M), Merlot blend (BW) red wine extracts, Ilex paraguariensis (Ip) or Ilex brasiliensis (Ib) aqueous extracts, Vaccinium meridionale Swartz (mortiño) fermented extract (FE) , berry juice (BJ) and polyphenols-riched fractions of cocoa(PFC) against reperfusion injury. Isolated rat hearts were submitted to 20 min of global ischemia (GI) and 30 min of reperfusion (R). Other hearts were treated 10 min before GI and first 10 min of R with the extracts. CS, M, Ip, Ib and FE attenuated the myocardial dysfunction and oxidative damage whereas BW, BJ and PFC were ineffective. Paradoxically, PFR had the highest and BW similar scavenging activity than protective extracts. The beneficial actions were lost when nitric oxide synthase (NOS) was inhibited. These data indicate that "in vitro" antioxidant capacity of natural products is not primarily responsible for the cardioprotection being involved NO-dependent pathways.